Pengaruh Perlakuan PWHT terhadap Sifat Mekanis Sambungan Las TIG pada Baja Grade 91 - Halman; Ramly, Ismail; Fauzi, Yusuf Rizal (Journal of Energy, Materials, & Manufacturing Technology, 2025)
Grade 91 steel is a high-alloy steel widely used in power and petrochemical industries due to its resistance to high temperatures, oxidation, and corrosion. However, welding this steel requires post-weld heat treatment (PWHT) to reduce residual stresses and enhance toughness. This study analyzes the effect of varying PWHT holding times (0, 4, 8, and 12 hours) on the mechanical properties of TIG-welded Grade 91 steel using ER90S-B9 filler metal. Tensile and hardness tests were conducted to evaluate changes in strength and material resistance due to heat treatment. The results indicate that without PWHT, the heat-affected zone (HAZ) experiences a significant increase in hardness due to martensitic formation, which the risk of cracking and brittleness. Applying PWHT with a longer holding time effectively reduces hardness in the HAZ and weld zone, improving material toughness. However, excessive PWHT duration may lead to a reduction in tensile strength. Therefore, selecting optimal PWHT parameters is crucial to ensuring the reliability of welded structures in industrial applications.